1991
DOI: 10.1128/jvi.65.8.4204-4210.1991
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic suppression of a deletion mutation of the nonstructural gene of an influenza A virus

Abstract: The influenza A/Alaska/77 (H3N2) virus mutant 143-1 is temperature sensitive (ts) due to a spontaneous in-frame 36-nucleotide deletion in the nonstructural (NS) gene segment, which leads to a 12-amino-acid deletion in the NS1 protein. In addition, it has a small-plaque phenotype on MDCK cell monolayers. However, phenotypically revertant (i.e., ts+) viruses were isolated readily following replication of the 143-1 virus both in vitro and in vivo. In order to determine the genetic mechanism by which escape from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…The possibility of deleting large parts of the protein should reduce the probability of repairing the deletion or generating second-site suppressor mutations. It should, however, be considered that even deletion mutants might phenotypically revert by acquiring intragenic or extragenic suppressor mutations (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of deleting large parts of the protein should reduce the probability of repairing the deletion or generating second-site suppressor mutations. It should, however, be considered that even deletion mutants might phenotypically revert by acquiring intragenic or extragenic suppressor mutations (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…e Results previously reported (25) we evaluated the stability of the ts phenotype rather than the att phenotype itself because the cumulative experience with the transfectant viruses indicated that the ts mutations themselves specified attenuation and therefore are an appropriate surrogate marker for the att phenotype. The ts or att phenotype of influenza A viruses can be modified by reversion of mutant sequences as well as by the development of intragenic or extragenic suppressor mutations (21,26,27,29). Since diverse genetic mechanisms can act to alter the ts and att phenotypes, it is not surprising to observe that viruses with single ts mutations, or even those with two ts mutations on different genes, readily undergo genetic modification resulting in the loss of the ts or att phenotype following replication in vivo (13,24,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting example of regaining fitness after an extended in-frame deletion in the coding region of the genome was documented for a spontaneous mutant of influenza A virus (504). This mutant was missing 36 nt in the RNA segment coding for the NS1 protein and exhibited ts and small-plaque phenotypes.…”
Section: Negative-strand and Double-stranded Rna Virusesmentioning
confidence: 99%